2019
DOI: 10.1155/2019/9216809
|View full text |Cite
|
Sign up to set email alerts
|

An Online Degradation Feature Extraction Technique for Shore Bridge Gearbox Based on Morphological Fractal Dimension and Sliding Window Weibull Fitting

Abstract: Shore bridge and other port cranes have some working condition characters including high speed, heavy load, and large impact. In order to solve the degradation feature extraction issue of hoisting mechanism gearbox, an online degradation feature extraction technique based on morphological fractal dimension and sliding window Weibull fitting is proposed. Firstly, taking the vibration energy spectrum collecting from the gearbox as the online data source, the fractal dimension of the vibration energy spectrum dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…
Figure 4 Vibration sensors. Reproduced from Sun et al 26 . The full lifetime data are derived from the vertical vibration sensor of the high-speed input shaft of the hoisting gearbox is shown in this figure.
…”
Section: Instance Data Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…
Figure 4 Vibration sensors. Reproduced from Sun et al 26 . The full lifetime data are derived from the vertical vibration sensor of the high-speed input shaft of the hoisting gearbox is shown in this figure.
…”
Section: Instance Data Analysismentioning
confidence: 99%
“…The signal sampling frequency was 24 kHz, the sampling time was 1 s, and the sampling interval was set as 10 s.
Figure 5 Realistic diagram of a roller bearing fault. Reproduced from Sun et al 26 . When some faults occurred on the gearbox, the fault location was found at the high-speed input shaft roller bearing of the gearbox, and the failure mode was roller wear, the figure is shown in this figure.
…”
Section: Instance Data Analysismentioning
confidence: 99%
“…In nonlinear analysis methods, symbolic dynamics analysis is an effective signal analysis method. Symbolic dynamics is proposed as a theoretical foundation for studying, nowadays, the method are used in a series of fields such as network security 15,16 , biomedicine 17,18 , and mechanical engineering 19,20 . Based on symbolic dynamics, symbolic analysis methods can discretize the original signal to extract the major trend of the signal, At the same time, they can also remove the noise, further improving the analysis effect and computational efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Some typical indicators proposed include spectral kurtosis, 6,7 spectral L2/L1 norm, 8 kurtosis 9 etc. Considering the nonlinear and non-stationary character of mechanical vibration signals, a complexity analysis method is used based on information from entropy and fractal dimension and is usually employed in feature analysis of rotating machinery such as bearings and gears in recent years, such as modified multi-scale symbolic dynamic entropy, 10 LMDsample entropy, 11 multi scale permutation entropy, 12,13 morphological fractal dimension 14 etc. Some previous studies have shown that vibration signals of the quay crane have a certain degree of complexity character.…”
Section: Introductionmentioning
confidence: 99%